Sistem Pemilihan Umum Distrik sebagai Alternatif Reformasi Pemilu di Indonesia - Muhammad Redondo Angga Putra Ariyanta; Agus Riewanto; Andina Elok Puri Maharani (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2026)
The open proportional representation system currently used in elections for members of the People’s Representative Council in Indonesia is considered not yet fully capable of strengthening the representative relationship and public accountability between the people and their representatives. This situation has spurred a discourse on electoral reform, one aspect of which involves the implementation of a district-based electoral system. This study aims to analyze the compatibility of the district-based electoral system with the principle of popular sovereignty, as well as the possibility of changing the electoral system in accordance with the 1945 Constitution of the Republic of Indonesia, while also examining the relevance of the district-based electoral system as an alternative for electoral reform in Indonesia. This study is a normative legal study employing both a statutory and a conceptual approach. The legal materials used consist of primary and secondary legal sources, which were analyzed qualitatively. The results of the study indicate that the district electoral system does not conflict with the principle of popular sovereignty because popular sovereignty is, in essence, realized through a representative system that guarantees political representation and accountability. Furthermore, the 1945 Constitution of the Republic of Indonesia does not prescribe a specific electoral system model; therefore, changes to the electoral system fall under the legislature’s open legal policy. This study also found that the district electoral system has the potential to strengthen representation and public accountability compared to the open proportional system. Although each variant has its own advantages and disadvantages, the Two-Round System is a viable alternative worth considering in the context of Indonesia’s pluralistic society.